Meningitis: epidemiological aspects of reported cases in the state of Piauí, Brazil (Research, Society and Development, 2020)
Meningitis is an inflammatory disease that affects the membranes that protect the central nervous system. This study aimed to describe the epidemiological profile of reported cases of meningitis in the state of Piauí from 2010 to 2017. The present study consisted of a retrospective study with a descriptive approach with secondary data obtained through the Disease Information and Notification System ( SINAN). In this study we analyzed the reported cases of meningitis in the state of Piauí from 2010 to 2017. Statistical analysis and the elaboration of graphs and tables were performed using Microsoft Excel and TabWin 3.6. From 2010 to 2017, a total of 2,071 cases of meningitis in Piauí were reported in (SINAN) (average of 295.8 cases per year), of which about 61% of those diagnosed were male. In this period, there is a constant reduction in the number of confirmed cases and the incidence of the disease, ranging from 428 cases and 13.61 incidence rate per 100,000 inhabitants in 2010, to 129 cases and 4 incidence rate per 100,000 inhabitants. in the year 2017. When analyzing the distribution of age groups, adults from 20 to 39 years were the most affected by the disease and the male gender predominated in all years. Overall, the evolution of the disease in the last three years recorded in the study, there was an increase in the case fatality rate and underreporting.